KAJIAN PROSES PEMBELAJARAN SENI KRIA - Widiyastuti, Endang (Jurnal Inovasi Pendidikan, 2009)
The aim of this research is to know and to identify: (1) The teaching learning process of artistic skill of seventh grade students of State Junior High School in Surakarta, (2) The existing difficulties which occur in the teaching learning process of artistic skill, (3) The type of artistic skill which is given to the seventh grade students in order to express themselves. This research revealed that (1) before teaching learning process of cultural art, teachers make a study design, and formulate it into the lesson plan; teachers create various teaching methods according to the condition of participants, teaching materials, and school condition; teachers apply various methods in delivering subject matters; teachers use materials; teachers may utilize media and learning source in teaching. (2) the difficulties found in teaching learning process mainly occur in the activity of self-expression through works of art which is not yet maximum; the lack of practice room for the participants, and the place to keep participants' master pieces which is not yet available; the activity of practice requires much time and cost. (3) The applied fine art which is given is batik and decorative manner.